The Interpersonal Collaboration in Stroke Emergency Management in Primary Care: Evaluating the Effectiveness of the Medical Team: KOLABORASI INTERPERSONAL DALAM MANAJEMEN KEGAWATDARURATAN STROKE DI LAYANAN PRIMER: EVALUASI EFEKTIFITAS TIM MEDIS - Andreas, Adikia (JURNAL KESMAS DAN GIZI (JKG), 2023)
.